DEVELOPING CITIZEN SCIENCE CONCEPT ON HILAL OBSERVATION IN INDONESIA - Dimas Firdaus, Muhammad
Hilal observation is the most celestial observation that people do in Indonesia. Observers from many communities always participate in observation sites, especially on Ramadan, Syawal, and Zulhijah. Most of the observers are not professional scientists, so this condition opens the opportunity to develop a scientific concept that can be implemented by people (citizen science). Citizen science is not a new concept in scientific research. Research that people conduct with a supervision from professional scientists can have many positive impacts on developing science in Indonesia. To obtain a good result from the observation, a proper procedure of observation is required so the research that people do has valid data and can be accounted for. An initial data collection related to real condition in the implementation of hilal observation, both in terms of the availability of human resources and the completeness of the instruments in various locations was carried out so that appropriate procedures can be formulated and expected to produce the similar hilal data. Then, in order to fulfill the citizen science concept, a platform is also designed to accommodate all hilal observation data which can be accessed widely by everyone to developed in further research.